Modeling ore quality using ore caving technique - Vladimir Ivanovich Golik; Viktor Grigoryevich Lukyanov; Vitaly Ivanovich Komashchenko (Известия Томского политехнического университета: Инжиниринг георесурсов, 2016)
Relevance of the research is caused by the need to expand the application of sublevel caving with front draw owing to the trend of mining conversion to underground method. The conversion is limited by a high level of ore losses and dilution. The aim of the research is to study the possibility of reducing ore technical losses and dilution by rocks crumble at ore draw form the chambers by optimizing the design parameters of the system as a condition to ensure the profitability of the technique applied. Methods: analysis of the advanced experience in developing similar fields based on publications, physical modeling of extraction cleaning parameter and forecasting the ways of developing the technique. Results. The paper introduces the results of research in field and laboratory conditions. The efficiency of the technique with the collapse reduces due to decrease of breaking arrays. The authors have confirmed the logical relationship between the parameters of ore draw and their quality and recommended the optimal parameters of excavation panels. It was ascertained that the chamber 80 C decline enhances the quality indices. When extracting ore with the options with sublevel caving with front draw the parameters of the mining method: width and depth of a draw figure and volume of ore, drawn before dilution that enables controlling the quality of the extracted ore, are correctly aligned. The main factors of improving the extraction rates are the increase of substage height and checkerboarding of outlets with the 25 m increased height of ore bed and the distance between the unit vectors of 8 m. Conclusions. Ore extraction from bowels by the outlets checkerboarding scheme at the increased height of ore bed provides economic benefits due to reduce of the amount of first workings, allows decreasing the number of active stopes due to the growth of ore volume in a breaking layer, increasing concentration of mountain works and loading and haulage equipment congestion.